Oor die bestaan van God en oor niksheid - Labuschagne, Kobus (Hervormde teologiese studies, 1997)
On the existence of God and on nothingness The views of Karl Barth and the 'Heilsgeschichte'-tradition on the one hand, and those of Rudolf Bultmann and the 'Formkritik'-tradition on the other hand, do not differ so much on the method of objective historical research. The real differences start to appear on the hermeneutical front, where facts and events referred to in the Scriptures are evaluated and explained. The 'Heilsgeschichte' -tradition is consistent in maintaining an objective point of departure, whilst Bultmann and the 'Form-kritik'-tradition, influenced by existentialist philosophy, reveals a subjective approach. For Bultmann the kerygma cannot be verified historically but only subjectively or existentially. For Barth the kerygma cannot be separated from its true basis of historical events, in and through the person of Jesus Christ. These two different approaches have enormous con-sequences for the question of the existence of God.